Early functional and structural hippocampal impairment in a bilateral common carotid artery stenosis mouse model - Ping Tang; Yi Sun; Chunsheng Yang; Nan Zhang (Animal Models and Experimental Medicine)
Abstract Background Subcortical ischemic vascular dementia (SIVD) is a common subtype of vascular dementia. Currently, the bilateral common carotid artery stenosis (BCAS) mouse model is the most suitable SIVD rodent model. In this study, we investigated the functional and structural impairments in the hippocampus 1 month after BCAS. Methods We used behavioral tests, laser speckle flowmetry, long‐term potentiation, histochemical staining, molecular experiments, and voxel‐based morphometry to evaluate the hippocampal impairments. Results Behavioral studies revealed that BCAS mice exhibited worse performance. Laser speckle flowmetry detected an obvious decrease in cerebral blood flow. The synaptic plasticity of the perforant path‐dentate gyrus pathway was inhibited. Decreased fractional anisotropy and increased mean diffusivity were detected in the hippocampus via diffusion tensor imaging data. A reduction in gray matter volume, which was most prominent in the hippocampus and its surrounding areas, was detected via voxel‐based morphometry analysis. Impairments in cell morphology and myelin integrity were validated using histochemical staining and molecular biology techniques. In addition, the numbers of GFAP+ astrocytes and Iba1+ microglia increased in the hippocampus. Conclusions Overall, our study demonstrates early functional and structural impairments in the hippocampus contributing to learning and memory deficits after 1 month of BCAS, indicating that the hippocampus is vulnerable to chronic cerebral ischemia.